Novel magnetic nanoparticles coated by benzene- and β-cyclodextrin-bearing dextran, and the sorption of polycyclic aromatic hydrocarbon. (20th November 2015) - Cho, Eunae; Tahir, Muhammad Nazir; Choi, Jae Min; Kim, Hwanhee; Yu, Jae-Hyuk; Jung, Seunho
Highlights: Magnetic nanoparticles (MNPs) coated by dextran derivatives are newly synthesized. Bz-Dex_MNPs and β-CD-Dex_MNPs showed sorption of PAHs by supramolecular chemistry. The prepared dextran derivative grafted MNPs can be recovered and recycled. Abstract: We present the synthesis of novel magnetic nanoparticles functionalized by benzene- and β-cyclodextrin-derivatized dextran. The grafting strategy was based on the [alkynyl-iron] cluster in the modified dextrans, which were prepared by click reaction from alkyne-modified dextran and benzyl azide or mono-6- O -deoxy-monoazido β-cyclodextrin. Characterization was then carried out by thermogravimetric analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, and vibrating sample magnetometry. Using the developed magnetic nanoparticles, the potential for removing polycyclic aromatic hydrocarbons such as phenanthrene and pyrene by sorption onto the nanomaterials was assessed. In the sorption, pi-stacking interactions of the benzene-derivatized dextran and host–guest chemistry of the β-cyclodextrin-derivatized dextran were considered to be significant. Furthermore, the polysaccharide derivative-coated magnetic adsorbents could be recovered by an external magnet for reuse.